Synthesis of metapristone through an efficient N-demethylation of mifepristone. Issue 9 (18th January 2016) - Wu, Jianlei; Yu, Xuemei; Liu, Jian; Lin, Yuqin; Gao, Yu; Jia, Lee; Chen, Haijun
Abstract : An improved and efficient condition of N -demethylation of mifepristone in an excellent yield is described. Abstract : Accumulating evidence demonstrates that mifepristone (RU486) exhibits potent anti-proliferative effects on various cancer cell lines. Our recent work shows that its major metabolite metapristone (RU42633) is a good drug candidate for cancer metastatic chemoprevention. However, lack of an efficient method for synthesizing metapristone limited its further clinical development. Herein, an improved and efficient condition of N -demethylation of mifepristone with an excellent yield is described. The procedure presented here has several advantages including one-pot preparation, ease of synthesis, and large-scale feasibility.